Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
(-2, 11) and (2, 3)
Step-by-step explanation:
Given system of equations:
1) f(x) = x² - 2x + 3 ⇒ y = x² - 2x + 3
2) f(x) = -2x + 7 ⇒ y = -2x + 7
Solve Using the Substitution Method:
Step 1: Substitute the the first equation into the second.
⇒ x² - 2x + 3 = -2x + 7
Step 2: Solve for x.
x² - 2x + 3 = -2x + 7 [ Add 2x to both sides. ]
x² - 2x + 2x + 3 = -2x + 2x + 7
⇒ x² + 3 = 7 [ Subtract 3 from both sides. ]
x² + 3 - 3 = 7 - 3
⇒ x² = 4 [ Take the square root of both sides. ]
√x² = √4
x = ± 2
⇒ x = -2, x = 2
Step 3: Solve for y.
Substitute the found x-values into one of the given equations.
y = -2x + 7 ⇒ y = -2(-2) + 7 ⇒ y = 4 + 7 ⇒ y = 11
y = -2x + 7 ⇒ y = -2(2) + 7 ⇒ y = -4 + 7 ⇒ y = 3
The solutions to the system of equations are: (-2, 11) and (2, 3).
Learn more about system of equations here:
brainly.com/question/26094713
brainly.com/question/27850666
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.